Perspektif Filsafat Cartesian dalam Bimbingan dan Konseling - Idat Muqodas (Journal of Innovative Counseling : Theory, Practice, and Research, 2017)
The basic substance of Cartesian philosophy is God, Mind and Material. Descartes philosophical views have contributed to the development of the science of Psychology and Counseling, especially theories that put forward the concept of "self". That view childbirth counseling approaches that focus on client centered and one of the most powerful influences that approach focuses on cognitive counseling. Impacts of Descartes the view that many western streams counseling theory that the exclusion of God's role in the practice of guidance and counseling. So theories of counseling west flow looks like secular theory.